Association of endothelin-converting enzyme and endothelin-1 gene polymorphisms with essential hypertension in Malay ethnics - Salim, Elnaz; Ramachandran, Vasudevan; Ansari, Neda; Ismail, Patimah; Mohamed, Mohd Hazmi; Mohamad, Nur Afiqah; Inche Mat, Liyana Najwa (Cambridge University Press, 2022)
Objectives. Endothelin-1 (ET-1), the most potent endogenous vasoconstrictor, generated by enzymatic cleavage catalyzed by an endothelin-converting enzyme (ECE), plays a significant role in the regulation of hypertension. Methods. This study investigates the effect of endothelin-1 (Lys198Asn/rs5370) and ECE (rs212526 C/T) gene polymorphisms with essential hypertension (EH) among Malay ethnics. To determine the association of gene polymorphism, 177 hypertensives and controls (196) were genotyped using Taqman method. Results. A significant difference was observed in ET-1 rs5370 and ECE rs212526 gene polymorphisms between EH and control subjects (P < 0.001). A significantly high body mass index (BMI), waist-to-hip ratio, fasting plasma glucose, hemoglobin A1c, systolic and diastolic blood pressure, and lipid profiles were observed among the EH patients when compared to controls (P < 0.05). Moreover, T allele (rs5370) carriers in males have a high risk for EH. There was no significant association between gender in ECE C/T polymorphisms (P > 0.05). Conclusion. Based on our result, it is evident that the T allele of ET-1 rs5370 polymorphism and C allele of ECE rs212526 have a significant genetic risk factor in EH among Malay subjects, and BMI and age are associated with hypertension.